The City Charter with the Several Laws Amendatory Thereto and the Revised Ordinances of the City of Peoria, Illinois 254 (James M. Cunningham ed., 1857) - (:unkn) unknown (My University, 1869)
Prohibited the discharge of any cannon, musket, rifle, fowling-piece, pistol, or other fire-arms or air-guns. Violators fined not less than one but no more than one hundred dollars. Violators also forfeit the weapon.
Keywords: DISCHARGE